Antivirus effectiveness of ivermectin on dengue virus type 2 in Aedes albopictus. - Tie-Long Xu; Yin Han; Wei Liu; Xing-Ya Pang; Bin Zheng; Yi Zhang; Xiao-Nong Zhou (Public Library of Science (PLoS), 2018)
Background Dengue fever is the most rapidly spreading mosquito-borne viral disease over the past 50 years, with a 30-fold increase in global incidence. Dengue vector control is a key component for the dengue control strategy, since no absolutely effective vaccine or drug is available yet. However, the rapid rise and spread of mosquito insecticide resistance have become major threats to the efficiency of insecticide-based vector control activities. Thus, innovative vector control tools are badly needed. This study aims to confirm the antivirus effectiveness of ivermectin on dengue virus type 2 (DENV-2) in Aedes albopictus (Skuse, 1894), then to explore its potential use in the combating to the dengue epidemics. Methods Aedes albopictus were first infected with DENV-2 in human whole blood, and at the fourth day after infectious blood feeding, they were divided into eight groups. Seven of them were held for six days with access to 0, 2, 4, 8, 16, 32 and 64 ng/ml ivermectin, respectively, and the last one was set as a historical control group, which was stored at -80°C until being detected at the same time with the other groups. Each mosquito was detected using real-time fluorescent RT-PCR kit. DENV-2 RNA concentration (copies/ml) and infection rate in each group were compared. Results Both of quantitatively and qualitatively inhibiting effects of ivermectin have been detected in this study. Generally, DENV-2 replicated well in Aedes albopictus without ivermectin intervention, whose virus loads exhibited significantly higher when the mosquitoes were holding from 4 days to 10 days after infectious blood feeding. In contrast, with the treatment of ivermectin, the infection rate was reduced by as much as 49.63%. The regression equation between infection rates (Y2) and ivermectin concentration log2 values (X2) was obtained as Y2 = 91.41-7.21*X2 with R2 = 0.89. Conclusion Ivermectin can directly or indirectly inhibit DENV-2 multiplication in Aedes albopictus. Moreover, the actual concentration for application in zooprophylaxis needs to be confirmed in the further field trials.